Methodological practices in social movement research (Oxford, 2014)
"Social movement studies have grown enormously in the last few decades, spreading from sociology and political science to other fields of knowledge, as varied as geography, history, anthropology, psychology, economics, law and others. With the growing interest in the field, there has been also an increasing need for methodological guidance for empirical research. This volume addresses this need by introducing the main methods of data collection and data analysis as they have been used in past research on social movements. Unlike other volumes, the book offers a practical, how-to approach and not simply a review of the methodological literature. Each author writes on a method they are very familiar with, having used it extensively in their own work. And each chapter presents specific discussions on every stage of research: from research design to data collection and the use of the information gathered. Throughout, research dilemmas and choices are presented, illustrated, and discussed. The volume offers an essential point of references for anyone undertaking research on social movements."